2021
DOI: 10.1007/s00393-021-01104-1
|View full text |Cite|
|
Sign up to set email alerts
|

Apps in rheumatology

Abstract: Zusammenfassung Hintergrund Digitale Gesundheitsanwendungen (DiGA) halten in vielen Bereichen der Medizin Einzug und haben das Potenzial, die Patientenversorgung zu revolutionieren. In der Rheumatologie wäre der Einsatz bei der axialen Spondyloarthritis (axSpA) in Form einer Trainings- und Bewegungs-App denkbar. In einer repräsentativen Umfrage unter Patienten mit axSpA sollte daher ermittelt werden, ob eine solche App aktuell benötigt wird. Methodik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Axia is a class I medical device that was developed by Applimeda (Aachen, Germany), a startup founded by medical students, in close cooperation with the University Hospital of Würzburg and the DVMB. The app's design and content are based on a market analysis of other approved DHAs (8), the results of a survey among 435 axSpA patients (7), individual interviews with more than 50 patients, and recommendations from rheumatologists at the University Hospital of Würzburg. In addition, several physical therapists specialized in axSpA were closely involved in the development of all exercise programs.…”
Section: Development Process and Design Of Axiamentioning
confidence: 99%
See 3 more Smart Citations
“…Axia is a class I medical device that was developed by Applimeda (Aachen, Germany), a startup founded by medical students, in close cooperation with the University Hospital of Würzburg and the DVMB. The app's design and content are based on a market analysis of other approved DHAs (8), the results of a survey among 435 axSpA patients (7), individual interviews with more than 50 patients, and recommendations from rheumatologists at the University Hospital of Würzburg. In addition, several physical therapists specialized in axSpA were closely involved in the development of all exercise programs.…”
Section: Development Process and Design Of Axiamentioning
confidence: 99%
“…Preliminary Data: Despite these limitations, this study provides initial insights into the use, functionality, and user satisfaction of a new digital medical device. It highlights a novel form of digital exercise intervention highly sought after by German axSpA patients (7).…”
Section: Strength and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides training in physical therapy facilities and self-help groups, home-based disease-specific exercise programs have shown to improve disease activity (Bath ankylosing spondylitis disease activity index [BASDAI]), disease-specific functionality (Bath ankylosing spondylitis functional index [BASFI]), range of motion (Bath ankylosing spondylitis metrology index [BASMI]) and quality of life (ASQoL [ankylosing spondylitis quality of life], SF-36 [36-item short form survey]) [4][5][6][7]. Despite these clear recommendations, a recent survey among 435 axSpA patients of the German patient self-help association "Deutsche Vereinigung Morbus Bechterew" (DVMB) found that nearly 30% of German axSpA-patients exercise too infrequently [8]. This trend has been further exacerbated by the closure of physical therapy facilities, fitness centers, and self-help groups during the SARS-CoV-2 pandemic [8].…”
Section: Introductionmentioning
confidence: 99%